TECHNOLOGY OF CORES PRODUCTION IN MASS PRODUCTION OF CASTINGS - A. P. Melnilkov (Литьë и металлургия)
Prospects of technology Cold-box-amin for mass production of cores by computer approach in all spheres of machine-building are shown.